Associations between cognition, anxiety, depression, and residual dizziness in elderly people with BPPV - Sun, Jin; Ma, Xiaobao; Yang, Ying; He, Kuan; Wang, Wei; Shen, Jiali; Wang, Lu; Chen, Xiangping; Jin, Yulian; Yang, Jun; Chen, Jianyong (Frontiers in Aging Neuroscience, 2023)
Objective To investigate the associations between cognition, anxiety, depression, and residual dizziness after successful repositioning maneuvers in the elderly with benign paroxysmal positional vertigo (BPPV). Methods We enrolled 40 elderly patients with BPPV in our outpatient department. We used the Dizziness Handicap Inventory (DHI), Visual Analog Scale (VAS), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder Questionnaire-7 (GAD-7) to assess the degree of dizziness, anxiety, and depression of participants before repositioning therapy, respectively. At the 1-week follow-up after BPPV treatment, each participant will be reassessed and divided into a group with residual dizziness (RD) and a group without residual dizziness (NRD) based on the follow-up DHI score. The Mini-Mental State Examination (MMSE) evaluated the cognitive function of the participants. Results The age, gender, duration of BPPV, and involved semicircular canals in the two groups did not show a significant difference. The RD group scored significantly higher on the DHI (p = 0.006), GAD-7 (p < 0.001), and PHQ-9 (p = 0.002) before the repositioning treatment than the NRD group. The two groups had no significant difference in MMSE score (p = 0.381). Anxiety and depression scores before repositioning treatment significantly and positively correlated with follow-up DHI scores (r = 0.678 and 0.522, respectively), but the MMSE score did not significantly relate to it. The univariate linear regression showed that the DHI (p < 0.001), GAD-7 (p < 0.001), and PHQ-9 (p = 0.002) scores before treatment could predict residual dizziness. The multivariate linear regression showed that GAD-7 before treatment was the only significant predictor of residual dizziness (p < 0.001). Conclusion The level of dizziness, anxiety, and depression before treatment can predict residual dizziness after successful repositioning maneuvers in the elderly with BPPV. Anxiety may be the strongest predictor of residual dizziness after successful repositioning treatment in elderly BPPV patients.